Low birth weight and adverse pregnancy outcomes among women living with HIV and HIV-uninfected in Rwanda - Natalia Zotova; Athanase Munyaneza; Gad Murenzi; Gallican Kubwimana; Adebola Adedimeji; Kathryn Anastos; Marcel Yotebieng (PLoS ONE, 2025)
Introduction In utero exposure to HIV and/or antiretroviral therapy (ART) has been shown to be associated with stillbirth, preterm births, and low birth weight (LBW), but data from low-resource, high- HIV-burden settings remain limited. This study describes adverse pregnancy outcomes among Rwandan women living with HIV (WLWH) and HIV-uninfected women and examines associations between HIV, ART timing, and LBW. Methods This retrospective cohort study used antenatal care, delivery, and PMTCT registry data from the Central Africa International Epidemiology Databases to Evaluate AIDS (CA-IeDEA). Women with documented HIV status and recorded birth weights were included. Adverse outcomes were defined as LBW (<2,500 g), stillbirth, and preterm birth (<37 weeks gestation). Logistic regression was used to assess associations between maternal HIV status, ART timing, and LBW, adjusting for relevant covariates. Results and discussion Among 10,191 women with known HIV status and babies’ birth weights, 12.7% (n = 1,293) were WLWH. There were 47 stillbirths (0.5%) and 70 preterm births (0.7%). Among 10,037 term births, 366 (3.6%) were LBW. WLWH had significantly higher rates of stillbirth (0.6% vs. 0.4%, p < 0.05) and LBW (6.5% vs. 2.9%, p < 0.001) compared to HIV-uninfected women; preterm birth rates did not differ significantly. The adjusted odds of LBW among WLWH were 1.61 (95% CI: 1.08, 2.39), controlling for marital status, primigravidae, and maternal weight at admission. Among WLWH (n = 1,274), ART initiation prior to pregnancy was associated with 50% lower odds of LBW after adjusting for age and WHO stage. Conclusions Even among relatively healthy uncomplicated pregnancies in low-risk delivery settings and universal ART, WLWH experienced significantly higher rates of stillbirth and LBW. Among WLWH, initiation of ART prior to current pregnancy had a protective effect against LBW. This underscores the importance of early HIV diagnosis and initiation of ART.